First report of Phyllorhiza punctata von Lendenfeld, 1884 (Cnidaria: Scyphozoa, Mastigiidae) in the Balearic Islands (Western Mediterranean Sea) - GONZÁLEZ, RAUL; CATANESE, GAETANO; VÁZQUEZ-LUIS, MAITE (Mediterranean Marine Science, 2024)
The white-spotted jellyfish Phyllorhiza punctata was first recorded in 1965 in the Mediterranean Sea. Here, we describe the first record of P. punctata in the Balearic Islands, specifically at the coastal lagoon Estany des Ponts, Alcudia, Mallorca. An adult individual and several juveniles were found in the summer months (July and August) of 2023, suggesting a preference for an increase in physicochemical variables, such as salinity and temperature. Molecular analysis performed on an adult individual allowed its genetic characterization. The small size and the low number of individuals found at this site suggest a recent invasion of this area of the Mediterranean Sea. Possible pathways for P. punctata’s arrival in this area have been suggested, but further monitoring is required to evaluate the evolution of P. punctata communities in this region in the subsequent years and to establish, conservation strategies in the upcoming years.